Chromatin-Mediated Regulation of Genome Plasticity in Human Fungal Pathogens - Buscaino, Alessia (Genes (Basel), 2019)
Human fungal pathogens, such as Candida albicans, Aspergillus fumigatus and Cryptococcus neoformans, are a public health problem, causing millions of infections and killing almost half a million people annually. The ability of these pathogens to colonise almost every organ in the human body and cause life-threating infections relies on their capacity to adapt and thrive in diverse hostile host-niche environments. Stress-induced genome instability is a key adaptive strategy used by human fungal pathogens as it increases genetic diversity, thereby allowing selection of genotype(s) better adapted to a new environment. Heterochromatin represses gene expression and deleterious recombination and could play a key role in modulating genome stability in response to environmental changes. However, very little is known about heterochromatin structure and function in human fungal pathogens. In this review, I use our knowledge of heterochromatin structure and function in fungal model systems as a road map to review the role of heterochromatin in regulating genome plasticity in the most common human fungal pathogens: Candida albicans, Aspergillus fumigatus and Cryptococcus neoformans.